Does combined cognitive training and physical activity training enhance cognitive abilities more than either alone? A four-condition randomized controlled trial among healthy older adults - Shatil, Evelyn (Frontiers in Aging Neuroscience, 2013)
Cognitive training and aerobic training are known to improve cognitive functions. To examine the separate and combined effects of such training on cognitive performance, four groups of healthy older adults embarked on a four months cognitive and/or mild aerobic training. A first group (n=33, mean age=80 [66-90]) engaged in cognitive training, a second (n=29, mean age=81 [65-89]) in mild aerobic training, a third (n=29, mean age=79 [70-93]) in the combination of both and a fourth (n=31, mean age=79 [71-92]) control group engaged in book-reading activity. The outcome was a well validated multi-domain computerized cognitive evaluation for older adults. The results indicate that, when compared to older adults who did not engage in cognitive training (the mild aerobic and control groups) older adults who engaged in cognitive training (separate or combined training groups) showed significant improvement in cognitive performance on Hand-Eye Coordination, Global Visual Memory (working memory and long-term memory), Speed of Information Processing, Visual Scanning and Naming. Indeed, individuals who did not engage in cognitive training showed no such improvements. Those results suggest that cognitive training is effective in improving cognitive performance and that it (and not mild aerobic training) is driving the improvement in the combined condition. Results are discussed in terms of the special circumstances of aerobic and cognitive training for older adults who are above 80 years of age.